Carbon resilience calibration as a carbon management technology - Talebian, Seyedeh Hosna; Jahanbakhsh, Amir; Maroto-Valer, M. Mercedes (Frontiers in Energy Research, 2023)
In the path to a net-zero carbon and energy transition from fossil fuel, the world is facing a dilemma of growing global energy demand and required actions on climate-related risks. While over 80% of the current global energy needs are supplied by fossil fuels, the number of carbon capture, utilization and storage (CCUS) projects is limited in this sector. There is a huge gap between the scale and distribution of ongoing CCUS projects and the carbon intensity (CI) of energy-intensive industries. Furthermore, the climate impact of growing reliance on unconventional resources (Tar sands and shales) as well as the depletion of conventional resources poses challenges to the oil and gas sector to meet energy demand, while limiting their greenhouse gas (GHG) emissions. On the other hand, the economic viability of CCUS projects is highly sensitive to carbon credits policies, which are not yet fully integrated in a way to fill the current gap in the number, scale and distribution of these projects. Moreover, there is limited consistency between the allocated decarbonization funds and the anticipated economic growth of fossil fuel economies to promote wide-scale global resilience to carbon exposure. Therefore, it is essential to take climate-related risks, including socioeconomic impacts, into consideration for the decision-making process of companies and governments to embrace low-carbon energy. The focus of this article is on carbon resilience calibration and emissions scenario analysis in investment decisions to realize decarbonization goals through balancing short-term actions with long-term energy transition plans. The challenges and prospects of the application of CCUS technologies as an industrial decarbonization approach are discussed. Carbon footprint (CFP) observing, factoring and reporting workflows for correlating carbon exposure and resilience as part of climate assessment are introduced. Moreover, the main elements of carbon resilience scenarios are analyzed to fill the gap between the current industrial activities and decarbonization plans and to avoid making decisions solely based on economic aspects. Finally, we propose a workflow for carbon resilience calibration and a cash flow model for a sample CCUS project in the upstream oil and gas industry.